Integrasi Pendidikan Islam Dalam Sistem Pendidikan Nasional - Dainuri Dainuri (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstarct: Our country, which is religious as a Muslim, of course, which has meaning in Islamic education itself which will be given to the next generation of the nation must have more quality for their dynasty and the hereafter. Islamic education whose essence is based on the true values of Islamic teachings will be used as a guide to live life in the world and be ended later. But with the current era of globalization making Islamic education itself can also change from conceptual-theoretical problems, to practical-operational problems. The role of education is very important in human life and cannot even replace the process of human life. In other words, human needs for education are included in personal life, family and society, nation and state. If the education system works optimally it will achieve the progress it aspires to and if it cannot achieve the desired progress. However, there are many criticisms that are used by various groups on education, or of course on the practice of education, but almost all parties that are in accordance with the community or the future are very profitable for their contribution to education. For example, very confident that education can provide energy on tomorrow. We can also read the same opinion in the General Explanation of the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System (Law No. 20/2003), others are: Humans need education in their lives. Education is an effort so that humans can develop their potential through a learning process or other means known and recognized by society